A Marginalised Adaptogen Withania somnifera (L.): Efficient Protocol for Conservation - Mishra, Tulika (Cutting Edge Research in Biology Vol. 1, 2022)
Aim of Study: Withania somnifera is a well-known medicinal plant since ages and in the recent Corona time, it is well popularised for being an immunity booster. Since the roots are mainly used for extraction of different bio-functional chemicals. The plant is facing severe conservation issues and is depleting from the wild. In vitro micropropagation technique and biotechnological interventions for extraction of secondary metabolites from callus can be an answer to sustainable growth and seal the gap in the demands for pharmaceutical industries. Withania somnifera (Ashwagandha) is an adaptogenic plant used in traditional medicine from ancient times of Ayurveda in Indian pharmacopeia. The present chapter discusses W. somnifera as an adaptogen which enhances the immunity and it is in need of urgent conservation protocol. The diverse active constituents present in different parts of the plant show various pharmacological activities such as anti-tumorigenic, anti-neurodegenerative, anti-anxiolytic, anti-inflammatory, antimicrobial, and hypolipidemic activities, among others. As a result of these benefits, Aswagandha is widely commercialised around the world, and many countries are investigating the use of W. somnifera as a food supplement and in a variety of other products. The roots of this plant are the most commonly used parts, putting a strain on the species' population. The conservation and sustainable use is the key to protect this plant. Direct Organogenesis through in micropropagation of this species showed good results.